Biodegradable manganese-doped hydroxyapatite antitumor adjuvant as a promising photo-therapeutic for cancer treatment - Park, Sumin; Choi, Jaeyeop; Doan, Vu Hoang Minh; O, Se Hwi (Frontiers in Molecular Biosciences, 2022)
The efficiency of a cancer therapy agent depends on its ability to eliminate tumors without endangering neighboring healthy tissues. In this present study, a novel multifunctional property enriched nanostructured system was synthesized on manganese-doped hydroxyapatite (Mn-HAp) conjugated with counter folic acid (FA) IR-783 fluorescence dye. The tailored synthesis of nano rod-shaped Mn-HAp nanoparticles with high surface area allows to conjugate FA/IR-783 dye which enhanced retention time during in vivo circulation. The drug-free Photothermal Photodynamic therapy mediated cancer treatment permits the prevention of collateral damages to non-cancerous cells. The safe HAp biomaterial matrix allows a large number of molecules on its surface due to its active different charge moieties (Ca2+ / PO4 3-) without any recurrence toxicity. The doped Mn allows releasing of Mn2+ ions which triggered the production of toxic hydroxyl radicals (•OH) via Fenton or Fenton-like reactions to decompose H2O2 in the tumor sites. Herein, IR-783 and FA were selected for targeted fluorescence imaging-guided photothermal therapy. 6The PTT performance of synthesized nanostructured system shows enhanced potential with ~60°C temperature elevation with 0.75W/cm2 power irradiated within 7 minutes of treatment. PDT activity was also observed initially with Methylene Blue (MB) as a targeted material which shows a drastic degradation of MB and further in vitro studies with MDA-MB-231 breast cancer cell line show cytotoxicity due to the generated reactive oxygen species (ROS) effect. FA/IR-783 conjugated Mn-HAp nanoparticles (2.0 mol% Mn-HAp/FA-IR-783) show significant tumor-specific targeting and treatment efficiency while intravenously injected in (tail vain) BALB/c nude mice model without any recurrence. The synthesized nanostructured system had ample scope to be a promising Photo-Therapeutic agent for cancer treatment.